An exploration of financing preferences among entrepreneurs: the case of micro enterprises in Kelantan, Malaysia - Adonia, Siti Azirah; Ahmad, Kamilah; Mohamed Zabri, Shafie (WSEAS, 2018)
Financing plays an important role in supporting micro enterprises development. Although there are many financing options made available for this sector, most micro-enterprises encounter problems in accessing the funding assistance due to some external issues. This paper aims to examine the financing preference among micro enterprises and the reasons that contribute to their financing preference. Data were derived from the questionnaire survey among the micro-enterprises entrepreneurs in Kelantan Malaysia. Based on 100 usable responses, the results demonstrate that the majority of the respondents rely heavily on their own funds due to loan application bureaucracy and owner/managers reluctance for additional debt commitment. The results also indicate that the respondents who opt for external debt financing, are triggered mainly by the insufficiency of their own internal capital for business expansion. In addition, respondents tend to use external funding if the loan application process is quick and simple with no collateral requirement. This is the case of most government micro-loan schemes where approval requirements are less rigid. This paper provides an insight in financing preferences among micro enterprises especially in a developing country.